Hepcidin is suppressed by erythropoiesis in hemoglobin E β-thalassemia and β-thalassemia trait. - Jones, E; Pasricha, SR; Allen, A; Evans, P; Fisher, C; Wray, K; Premawardhena, A; Bandara, D; Perera, A; Webster, C; Sturges, P; Olivieri, N; et al. (2014)
HbE β-thalassemia is the most common severe thalassemia syndrome across Asia, and millions are carriers. Clinical heterogeneity in HbE β-thalassemia is incompletely explained by genotype, and the interaction of phenotypic variation with hepcidin is unknown. The effect of thalassemia carriage on hepcidin is also unknown, but could be relevant for iron supplementation programs aimed at combating anemia. In 69 Sri Lankan HbE β-thalassemia patients with moderate or severe phenotype, hepcidin was suppressed in 62/69 patients, and overall hepcidin inversely correlated with iron accumulation. On segregating by phenotype, there were no differences in hepcidin, erythropoiesis or hemoglobin between severe or moderate disease, but multiple linear regression showed that erythropoiesis inversely correlated with hepcidin only in severe phenotypes. In moderate disease, no independent predictors of hepcidin were identifiable; nevertheless the low hepcidin levels indicate a significant risk of iron overload. In a population survey of Sri Lankan schoolchildren, β-thalassemia (but not HbE) trait associated with increased erythropoiesis and mildly suppressed hepcidin, suggesting an enhanced propensity to accumulate iron. In summary, the influence of erythropoiesis on hepcidin suppression associates with phenotypic disease variation and pathogenesis in HbE β-thalassemia, and indicates the epidemiology of β-thalassemia trait requires consideration when planning public health iron interventions.